2020
DOI: 10.1186/s40635-020-00319-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluids in ARDS: more pros than cons

Abstract: In acute respiratory distress syndrome (ARDS), increased pulmonary vascular permeability makes the lung vulnerable to edema. The use of conservative as compared to liberal fluid strategies may increase the number of ventilator-free days and survival, as well as reduce organ dysfunction. Monitoring the effects of fluid administration is of the utmost importance; dynamic indexes, such as stroke volume and pulse pressure variations, outperform static ones, such as the central venous pressure. The passive leg rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…On the other hand, fluid therapy may worsen lung edema due to the altered permeability of pulmonary microvessels [ 17 ]. Therefore, the prediction of fluid responsiveness is important to test in patients with ARDS to prevent fluid administration in those who are fluid unresponsive and for whom harmful consequences of fluid therapy would be maximal [ 18 ]. Pulse pressure variation (PPV), passive leg raising (PLR), and end-expiratory occlusion (EEO) are dynamic variables or tests that are commonly used to predict fluid responsiveness in mechanically ventilated patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fluid therapy may worsen lung edema due to the altered permeability of pulmonary microvessels [ 17 ]. Therefore, the prediction of fluid responsiveness is important to test in patients with ARDS to prevent fluid administration in those who are fluid unresponsive and for whom harmful consequences of fluid therapy would be maximal [ 18 ]. Pulse pressure variation (PPV), passive leg raising (PLR), and end-expiratory occlusion (EEO) are dynamic variables or tests that are commonly used to predict fluid responsiveness in mechanically ventilated patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by reducing the messenger RNA and protein expression of myocardial nitric oxide synthase II ( 32 ). The decrease in serum albumin levels may affect the integrity of the endothelial layer of the heart, and supplementing with albumin can help maintain this important barrier and further reduce inflammatory responses ( 33 ). During the formation of atherosclerosis, the overactivity of platelets will release a variety of proinflammatory and growth factors, which will aggravate the formation of vasculitis and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the lungs, albumin promotes the maintenance of the glycocalyx layer, reduces inflammation, and improves alveolar-capillary membrane permeability [27]. A study of 993 ICU patients at the Vanderbilt University Medical Center concluded that lower serum albumin was independently associated with an increased risk of ARDS and that low plasma oncotic pressure contributes to pulmonary edema formation in patients at risk for ARDS within the first 72 hours after ICU admission [28].…”
Section: Sepsis-induced Ards Preventionmentioning
confidence: 99%